The transition from traditional banking to mobile internet finance: an organizational innovation perspective - a comparative study of Citibank and ICBC - Zhuming Chen; Yushan Li; Yawen Wu; Junjun Luo (Financial Innovation, 2017)
The development of Financial Technology (FinTech) in areas such as mobile Internet, cloud computing, big data, search engines, and blockchain technology have significantly changed the financial industry. FinTech is expected to overturn the traditional banking business model, forcing banks to upgrade and transform. This study adopts a comparative case study method to contrast and analyze the Industrial and Commercial Bank of China (ICBC) and Citibank. It analyzes the strategies, organizations, HR systems, and product innovations adopted by these two banks in response to the impact of FinTech. This paper proposes an 'electric vehicle' mode for ICBC and an 'airplane mode' for Citibank. Further, it describes the difficulties encountered by the Chinese banking industry and proposes some feasible ways to upgrade. 'Technology power' will become the core competitive concept for the financial institutions of the future.
Keywords: 650; Mobile Internet finance; Traditional banks; Upgrade and transformation; Organizational innovation; Technology power